Information System Strategic Planning in Improvement College Competitiveness (XYZ University) - Supriyadi, Hari (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to design an information system strategy plan in synergizing business processes that are carried out with the development of an organization's information system strategy, this is done as an organizational reference in developing information systems that are in line with the implemented business strategy.The approach method used in designing information systems strategic planning at XYZ University in Bandung City implements collaboration between Enterprise Architecture Planning (EAP) with Ward & Peppard Framework as a framework for designing information systems strategic planning that aims to synergize the development of information systems and business strategies organization. The steps/stages are as follows: Analyzing the organization's internal and external situation/environment, Analyzing the internal and external situation/environment of information systems, Strategic planning of information systems and information system architecture, Mapping of information systems and information system portfolios, recommendations and roadmaps implementation.The findings of this study can be used as reference material in designing information systems strategic planning, it aims to integrate one part with other parts in order to achieve very good efficiency and effectiveness of inter-departmental processes. Further observations are needed in the future as a reference for strategic planning of information systems, this can help in developing the system because the frame of mind or roadmap of information systems is designed according to the needs of the organization.This research is expected to be a reference in designing information systems strategic planning that can synergize business strategy with information system development strategies according to organizational needs that can provide convenience in carrying out organizational business processes.